AUTHENTIC NOTARIAL DEED ISSUE OF ATTORNEY POWER APPLICATION TO CHARGE ON MORTGAGE RIGHTS - Dahniarti Hasana (International Journal of Law Reconstruction, 2021)
In progress, if a debtor himself is unable to register Deed of Granting Mortgage Rights application, then he may choose a representative. As a consequence of debtor's absence, deed of giving mortgage rights must be made into Attorney power to Charge for Mortgage Rights deed. This research is a sociological juridical research. the research results obtained In its development Article 96 PMNA/Perkaban No. 3 of 1997 as amended by Perkaban No. 8 of 2012 requires that deed be made in accordance with forms prepared by BPN or the Land Agency. This is clearly at odds with the provisions related to deeds of Article 15 paragraph (1) of Act No. 2 of 2014 which mentions that Notaries are authorized to make authentic deeds, not writing letters or filling in forms such as SKMHT form drafted by BPN. Therefore, it is clear that the current SKMHT has contradicted the provisions of Article 15 paragraph (1) of Act No. 2 of 2014.